Advances in Biologically Inspired Information Systems Models, Methods, and Tools - Dressler, Falko; Carreras, Iacopo (Studies in Computational Intelligence, 2007)
Technology is taking us to a world where myriads of heavily networked devices interact with the physical world in multiple ways and at multiple scales, from the global Internet down to micro and nano devices. Many of these devices are highly mobile and must adapt to the surrounding environment in a totally unsupervised way. A fundamental research challenge is the design of robust decentralized computing systems that are capable of operating under changing environments and noisy input, and yet exhibit the desired behavior and response time, under constraints such as energy consumption, size, and processing power. Biological systems are able to handle many of these challenges with an elegance and efficiency still far beyond current human artifacts. The goal is to obtain methods on how to engineer technical systems, which have similar high stability and efficiency. With this book, we present a comprehensive overview of the most promising research directions in the area of bio-inspired computing. According to the broad spectrum addressed by the different book chapters, a rich variety of biological principles and their application to ICT systems are presented.